PREVENTING AGGRESSION IN YOUTH: A SOCIAL ASPECT - Maria Сhmielewska (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article deals with the phenomenon of aggression as a social phenomenon that has both social and biological (psychological) conditions. Based on the analysis of scientific sources the author has classified the types of aggression, emphasizing that the typology depends on the division criterion. The research results are based on the most commonly used classification of aggression into physical, verbal (psychological) and self-aggression. Particular attention is paid to the socio-cultural determinants of aggression and violence among young people, including the models of aggression that young people observe in a close surrounding (family, educational environment) and in a remote surrounding (media, Internet, television programs). It has been stressed that the circumstances aggravating the manifestations of aggression are the use of alcohol, drugs, computer addiction. The article emphasizes that the likelihood of manifestation of aggressive forms of behaviour depends on the frequency of aggression in the environment, on manifestations of aggression by authority figures (for example, educators), on the observation of the benefits of aggression (for example, in the form of an advantage gained), as well as on the frequency of opportunities for aggressive behaviour. The article emphasizes that not only victims of aggression, but also aggressors need help. In order to counteract aggression as part of a young person's social life, it is not enough to identify the problem - it is important to eliminate the causes of aggression. Restricting, preventing and countering this phenomenon require an effective network of social services, as well as the activation of local communities. On the example of the programs for preventing and eliminating aggression in the Republic of Poland the author proves that assistance aimed at stopping aggression should be taken not only for a young person's personal well-being but also through the social and psychological consequences of this phenomenon.